Design of new modular metal pallets: Experimental validation and life cycle analysis. (February 2022) - Zacchei, Enrico; Tadeu, António; Almeida, João; Esteves, Miguel; Santos, Maria Inês; Silva, Samuel
Graphical abstract: Highlights: New modular metal pallets that combine blocks and deck boards are proposed. 3D FEM, analytical, and experimental tests are carried out and results compared. More reliable values for loadings and displacements are provided for steel pallets. A comparative LCA suggests that steel pallets have a good environmental performance. Abstract: Given the huge number of products transported worldwide every day, it would be advantageous to use lightweight pallets made of readily recyclable materials that are easy to clean, durable, and cheap to maintain. However, the design process for new metal pallets does not follow any specific code, which makes the transition to products with improved characteristics more challenging. This paper describes the development of a new modular steel pallet that combines blocks and deck boards to produce a range of configurable geometries for use in transportation (forklifting) and stationary (racking, stacking) conditions alike. Analytical and numerical analyses using the 3D finite element method (FEM) were carried out. Experimental tests were performed to evaluate ultimate strengths and deformations for different loadings. The experimental results used to validate the numerical models showed that these pallets performed well in terms of stiffness, deformation, and stresses. A comparative life cycle analysis (LCA) was also carried out to identify the main environmental impacts of the life cycle of pallets made from different materials. The results of a "cradle-to-gate with options" model suggest that the new proposed pallet performs better than its wood, plastic, and aluminium counterparts.